Applying various criteria to assess the nutritional status among hospitalised patients aged 65 and over - Ostrowska, Joanna Maria; Węgierek, Dorota Szostak; Steinhagen, Anna Jeznach (Progress in Nutrition, 2019)
Introduction: Malnutrition commonly occurs among hospitalised patients. Should the condition be diagnosed early, it is possible to counteract development of negative effects associated with a weight loss and the systemic consequences of malnutrition. Objective: To determine the prevalence of abnormal nutritional status in patients aged 65 and over using various criteria for diagnosis, as well as an analysis of correlations between the criteria that were used. Material and methods: The study included 102 patients over the age of 65 years. Basic anthropometric measurements and a body composition analysis were performed. An abnormal nutritional status was diagnosed based on the results of the MNA-SF test, laboratory tests (serum albumin levels, total lymphocyte count - TLC) and the European Society for Clinical Nutrition and Metabolism’s (ESPEN) 2015 criteria regarding nutritional status. Results: An abnormal nutritional status was found in 75% of the subjects. It was most frequently diagnosed based on the MNA-SF score (66%) and laboratory test results (53%), and most rarely based on a BMI measuring less than 18.5 kg/m2 (5%). There was no statistically significant correlation between a BMI < 18.5 kg/m2, the MNA-SF score and laboratory test results. The MNA-SF test score had the strongest correlation with results obtained using the ESPEN criteria which included a reduced fat-free mass index (FFMI) combined with an unexpected loss of body weight. Conclusions: Of the analysed criteria used to assess nutritional status, the MNA-SF screening tool and the laboratory test results had the highest sensitivity. In this age group, the ESPEN criteria including FFMI were the most useful, and the criterion based only on a BMI of less than 18.5 kg/m2 was the least useful.